(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This topic examines the role of cultural heritage sites in enhancing the tourism potential of Uzbekistan. Historical and architectural monuments, ancient cities, and national traditions serve as important factors that strengthen the country’s attractiveness in the international tourism market. In particular, historical centers such as Samarkand, Bukhara, and Khiva, along with their unique complexes - monuments such as Registan Square and Ichan Kala - are internationally recognized and included in the UNESCO World Heritage List. These cultural heritage sites play an important role in attracting tourists, developing the national economy, improving regional infrastructure, and preserving national culture. Moreover, the promotion of cultural heritage contributes to forming a positive image of the country and supports the development of sustainable tourism.